One-Year Outcomes Following Repair of Thoracoabdominal Aneurysms With the Multilayer Flow Modulator: Report From the STRATO Trial. (February 2014) - Vaislic, Claude D.; Noël Fabiani, Jean; Chocron, Sidney; Robin, Jacques; Costache, Victor S.; Villemot, Jean-Pierre; Marc Alsac, Jean; Leprince, Pascal N.; Unterseeh, Thierry; Portocarrero, Eric; Glock, Yves; Rousseau, Hervé
Purpose: To evaluate endovascular repair of type II and III thoracoabdominal aortic aneurysms (TAAA) using the Multilayer Flow Modulator (MFM) in patients with contraindications for open surgery and fenestrated stent-grafts. Methods: In this prospective, multicenter, nonrandomized trial (EudraCT registration: 2009-013678-42; ClinicalTrials.gov identifier NCT01756911), 23 patients (19 men; mean age 75.8 years) with Crawford type II (43.5%) and III (56.5%) TAAA (mean diameter 6.5 cm) were treated with the MFM between April 2010 and February 2011. The primary efficacy outcome measure was stable aneurysm thrombosis with associated branch vessel patency at 12 months; the primary safety endpoint was 30-day and 12-month all-cause mortality. Results: The rate of technical success was 100%. In 20 patients with computed tomography scans at 12 months, the primary efficacy outcome was met in 15 patients. The rate of primary patency of covered branch vessels was 96% (53/55); 1 patient with 2 occluded visceral branches underwent successful surgical reintervention. Endoleaks were identified in 5 patients (3 attachment site and 2 at device overlap), 4 of whom underwent reintervention (3 additional MFMs and 1 stent-graft implanted). At 12 months, aneurysm diameter was stable in 18 of 20 patients; the mean ratio of residual aneurysm flow volume to total volume had decreased by 28.9%, and the mean ratio of thrombus volume to total lumen volume had increased by 21.3% (n=17). There were no cases of device migration, loss of device integrity, spinal cord ischemia, or aneurysm rupture. Conclusion: At 1 year, endovascular repair with the MFM appears to be safe and effective while successfully maintaining branch vessel patency. Follow-up is ongoing.